CHARACTER VALUES LEARNING MODEL IN THE PERKAMPUNGAN BUDAYA BETAWI SETU BABAKAN AT THE ELEMENTARY SCHOOL LEVEL OF DKI JAKARTA - Ajat Sudrajat; Vina Iasha; Dewi Hartanti (JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
AbstractInnovative learning in the industrial era of 4.0 emphasizes strengthening the character values integrated into traditional culture or customs in an area. In the Betawi Cultural Village, in particular, Integrated Thematic Learning is integrated with various traditional arts to develop the character values contained therein. However, in the process of teaching and learning activities, the implementation still tends to be separate for each subject. This research aims to create a product of character values learning model. The method used in this research is research and development using the Borg & Gall model through seven stages. The type of data used in this research is quantitative and qualitative data. Based on the results of the trials in this research, shows that the learning model developed, overall can be used without revision. This is indicated by the validity level of the model developed at 90.5% with very valid criteria (can be used). While the practicality level is indicated by the acquisition of a score of 96.04% with very practical criteria (can be used), and the effectiveness of the product is seen with a score of 88.25% with very effective criteria (can be used). The results of developing a learning model based on group investigation in this thematic learning can be suggested to be studied and utilized by all students.Keywords: Innovative Learning; Character Values; Betawi Culture.